Compositional and functional shifts in arctic fungal communities in response to experimentally increased snow depth. (September 2016) - Semenova, Tatiana A.; Morgado, Luis N.; Welker, Jeffrey M.; Walker, Marilyn D.; Smets, Erik; Geml, József
Abstract: Climate warming leads to more intensive evaporation from the Arctic sea resulting in increased precipitation in the low Arctic, e.g., higher snowfall during winter. Deeper snow keeps the arctic soils warmer and alters soil attributes and vegetation, e.g., increase in nitrogen availability, expansion of shrubs and decline in shade-intolerant lichens and bryophytes. Changes in soil properties and vegetation are expected to influence on saprotrophic and plant-symbiotic fungi, but how increased snow depth affects their community composition remain unknown. In the present work, we used DNA metabarcoding to study the effects of long-term experimental manipulations of snow depth on soil fungal communities in dry heath and moist tussock tundra in Arctic Alaska. We report strong changes in fungal community compositions in the two tundra types, with pronounced declines observed in the majority of fungal functional guilds, including ectomycorrhizal, lichenized, plant pathogenic, saprotrophic and bryophyte-associated species. The observed changes in lichenized and bryophyte-associated fungi are in agreement with previously published above-ground changes, i.e. decrease of lichen and bryophyte cover and diversity. However, the majority of observed trends, including the decline of ectomycorrhizal fungi (that were anticipated to benefit from the expansion of their host plants), suggest that changes in fungal communities do not entirely correspond to and are not primarily driven by shifts in vegetation. Instead, arctic fungal communities appear to exhibit faster turnover that may be influenced by dynamic interactions with numerous biotic and abiotic factors, e.g., soil nutrient cycling and community dynamics in other groups of soil microorganisms. We highlight the importance of "below-ground studies" in assessing ecosystem responses to climatic changes, because faster turnover of microbial communities may be applicable for monitoring early-stage alterations caused by climatic changes. Highlights: Climate models predict increased winter precipitation in the Arctic. We found that increased snow pack strongly alters soil fungal communities. The majority of fungal functional guilds declines under deep snow. Shifts in fungal communities may be temporally decoupled from vegetation.